DIGITAL INFORMATION PLURALISM AND ISLAMIC SOCIAL AND RELIGIOUS ETHICS IN YOUTH POLITICAL ORIENTATION - Aflah, Fajirul; Wirman, Hardi Putra; Hendri, Novi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study analyzes the impact of digital pluralism on political party preferences from the perspective of Islamic Human Resource Management (HRM) in West Sumatra. This study aims to examine how pluralistic narratives on social media shape the perceptions and political choices of people with a strong religious-cultural basis. This study uses a quantitative descriptive-correlational approach, data collected through a survey of active social media users. The results of the statistical analysis indicate that the level of digital pluralism and Islamic HRM ethics are in the high category, while party preferences based on pluralistic imagery are classified as moderate. There is a significant correlation between digital pluralism and party preferences, with Islamic HRM ethics acting as a mediating variable. These findings indicate that the influence of pluralism in digital politics is only effective when integrated with substantive ethical values. The implication is that strengthening ethical human resource governance and leadership with integrity are important prerequisites for increasing democratic participation and political professionalism in the context of Islamic society.